2023
DOI: 10.1093/ptj/pzad088
|View full text |Cite
|
Sign up to set email alerts
|

“Restoring That Faith in My Shoulder”: A Qualitative Investigation of How and Why Exercise Therapy Influenced the Clinical Outcomes of Individuals With Rotator Cuff–Related Shoulder Pain

Abstract: Objective Rotator cuff-related shoulder pain is the most common form of shoulder pain. Exercise therapy is a first-line recommended treatment for rotator cuff-related shoulder pain. However, the causal mechanisms underpinning the beneficial effects of exercise for rotator cuff-related shoulder pain are not well understood. Moreover, how individuals with lived experience of rotator cuff-related shoulder pain believe exercise helped or did not help is unknown. This study aimed to gain insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…This is concordant with recent research illustrating that individuals often want and expect exercise from their physiotherapist, as described by a participant in the Subialka et al (2022) qualitative assessment (Jensen et al, 2022;Subialka et al, 2022): I'm just looking for them to teach me how to do the exercises I need to do at home to keep that range of motion going and to knock that pain level down without major surgery. (Subialka et al, 2022) A qualitative investigation exploring how and why individuals with lived experience of RCRSP believed exercise helped their symptoms reported that all participants in the study had a positive experience with exercise, but only under certain conditions (Powell et al, 2023).…”
Section: What Can We Learn From the Lived Experience Of Individuals W...mentioning
confidence: 99%
See 4 more Smart Citations
“…This is concordant with recent research illustrating that individuals often want and expect exercise from their physiotherapist, as described by a participant in the Subialka et al (2022) qualitative assessment (Jensen et al, 2022;Subialka et al, 2022): I'm just looking for them to teach me how to do the exercises I need to do at home to keep that range of motion going and to knock that pain level down without major surgery. (Subialka et al, 2022) A qualitative investigation exploring how and why individuals with lived experience of RCRSP believed exercise helped their symptoms reported that all participants in the study had a positive experience with exercise, but only under certain conditions (Powell et al, 2023).…”
Section: What Can We Learn From the Lived Experience Of Individuals W...mentioning
confidence: 99%
“…In 2017, the Lancet published the Right Care Series and defined the right care as 'care that is tailored for optimising health and wellbeing by delivering what is needed, wanted, clinically effective, affordable, equitable, and responsible in its use of resources' (Elshaug et al, 2017). Exercise for RCRSP is modestly effective (Babatunde et al, 2021;Naunton et al, 2020;Steuri et al, 2017), often desired (Maxwell et al, 2021;Powell et al, 2023;Subialka et al, 2022), relatively affordable, and cost-effective (Oppong et al, 2021). We submit that exercise is equitable and responsible in its use of resources, certainly when compared to surgery for the majority of cases (Lewis, 2022).…”
Section: Navigating Uncertainty: Theoretical Considerations For Using...mentioning
confidence: 99%
See 3 more Smart Citations